The Pitfall of VA ECMO management in the Impella era. (3rd October 2022) - Shibao, K; Kitamura, C; Matushima, Y; Yanai, T; Shibata, T; Honma, T; Otsuka, M; Fukumoto, Y
Abstract: Introduction: VA ECMO is effective in cardiogenic shock, but complications of cardiogenic pulmonary edema due to increased afterload are problematic. The advent of percutaneous left ventricular assist devices (Impella) has enabled effective reduction of left ventricular intraventricular pressure and has avoided these complications, but differential hypoxia can still occur during VA ECMO + Impella (Ecpella) management, requiring conversion to V-AV ECMO. Cases may be experienced. Purpose: Elucidate the frequency of differential hypoxia and its pathogenesis, which requires the transition from VA ECMO to V-AV ECMO. Methods: We retrospectively reviewed 52 consecutive patients who underwent E-CPR from January 2017 through November 2021 in our institute. 8 patients who received ECMO alone were excluded, and 44 patients were recruited. 22 patients underwent VA ECMO with IABP (VA ECMO + IABP group) and 22 patients underwent VA ECMO with Impella (VA ECMO + Impella group). The 30-day survival rate and the rate of transition VA ECMO to VA-V ECMO, The date just before VA ECMO to V-AV ECMO were assessed. Results: The 30-day all-cause mortality was no significant difference between the two groups. 2 patients (9%) in the VA ECMO + IABP group and 8 patients (36%) in the VA ECMO + Impella group were transferred to V-AV ECMO (P=0.025). At the time of addition of V-AV ECMO, SaO2 (right radial artery) was 87±7.1% and 91.3±1.9% (p=0.112) in the VA ECMO + IABP and VA ECMO + Impella groups, respectively, and the P/F ratio was 86±37.1 and 95±24.6 (p=0.685). Mean pulmonary artery wedge pressure was 23±1.4 mmHg in the VA ECMO + IABP group and 16.3±3 mmHg in the VA ECMO + Impella group (p=0.0193), significantly lower in the Impella group. Conclusion: The Impella group was more likely to have hypoxia due to factors other than cardiogenic pulmonary edema. In cases of cardiopulmonary arrest requiring V-AV ECMO management, differential hypoxia due to causes other than cardiogenic pulmonary edema may become apparent earlier in the Impella group, suggesting that careful management, including the addition of V-AV ECMO, is required. Funding Acknowledgement: Type of funding sources: None.